Constructivism in Maharoh Kalam Learning Using YouTube Content for ICP PBA 2022 Students at UIN Maulana Malik Ibrahim Malang - Hilmi, Danial; Bahagia, Anissa Fatih Nur Fadilah Putri (Universitas KH. A. Wahab Hasbullah, 2024)
This research aims to explore the Maharoh Kalam lectures for ICP PBA 2022 students using YouTube video content based on Constructivism Theory. This research uses a descriptive qualitative approach which uses data collection techniques using interviews and observations. This research produces several conclusions, First, there are several steps that students must pay attention to, including, (1) Before the project begins, lecturers ensure that students can access the YouTube application and have an account, (2) prepare an account that will be used during lectures, and (3) conducting lectures that apply Constructivism theory in the video production process. Second, researchers found several student obstacles during the process of executing the video assignment, such as students' lack of confidence in uploading on their accounts. Third, from the results of this research, the researcher concluded that learning using YouTube media forms positive perceptions of students, including students experiencing increased Public Speaking skills. On the other hand, some students experience a tendency towards social media because they get assignments online. Researchers suggest conducting further research regarding the integration of other learning theories into Arabic language learning using social media.